Registration and documentation in the Archaeology Service (The International Journal of Educational Sciences and Arts, 2025)
Cultural artifacts and archaeological sites receive great attention from individuals, institutions and countries alike, due to their effective role in preserving the cultural, social and historical identity of nations and peoples. Therefore, we find that preservation and restoration methods and their consequences take top priority from those in charge of heritage and archaeological sites. Perhaps one of the most important topics related to this is the archaeological registration and documentation processes for artifacts and archaeological sites, which contain many sciences and knowledge that help in these processes. The archaeological registration and documentation processes have many benefits for heritage artifacts and archaeological sites, as they undoubtedly help first in the dating processes of these artifacts and archaeological sites, and they also help in identifying the changes associated with the impact of time or encroachment that occurred on these heritage artifacts. Perhaps the most prominent use of registration and documentation processes comes within the provisions of the preservation and restoration plan, as they help in identifying the chemical composition and different characteristics of these artifacts, which helps in developing the appropriate preservation and restoration plan, and also choosing the appropriate materials for restoration processes. The registration and documentation processes in this case accompany the restoration steps from the beginning to the end, which helps the researchers to highlight the aesthetic and cultural values ​​of these holdings and present them to those interested and the next generations, and to facilitate their handling and preservation in the future. In this paper, everything related to the registration and documentation process will be discussed, its importance and its role in serving antiquities in general, to clarify how to optimally use registration and documentation in the field of antiquities.
Keywords: Registration; Documentation; Antiquities; Examinations; Dating; Restoration; Digitization